Effect of neutralizing substances on the content of trace elements in soil contaminated with cobalt - Kosiorek, Milena; Wyszkowski, Mirosław (Oficyna Wydawnicza Politechniki Wrocławskiej, 2019)
The aim of the study was to determine the effect of increasing doses of cobalt (0, 20, 40, 80, 160, 320 mg/kg d.m. of soil) on the total content of trace elements in soil after application of manure, clay, charcoal, zeolite and calcium oxide. The neutralizing substances were applied at 2% of the soil weight, and calcium oxide at a dose corresponding to one hydrolytic acidity. The content of the cobalt, cadmium, lead, chromium, nickel, zinc, copper, manganese and iron was determined in soil. The contamination of soil with cobalt and the application of neutralizing substances had significant effects on the total content of trace elements in soil In the series without substances, the soil contamination with cobalt increased the content of cobalt, lead, chromium, nickel and zinc in soil. All the neutralizing substances reduced the content of cobalt, manganese and iron in soil. The highest decrease in the cobalt content was observed in the series with manure, whereas the highest decrease in zinc occurred after addition of charcoal. The decrease in the content of the other metals (except nickel and lead) was observed in the pots with CaO and zeolite. The effect of other neutralizing substances depended on the trace element.
Environment Protection Engineering. Vol. 45, 2019, nr 1, s. 45-55
Keywords: ochrona środowiska; inżynieria środowiska